Implementasi Peraturan Daerah No 9 Tahun 2009 tentang Retribusi Pelayanan Pasar - Anniza Cahya Kusuma; Aufarul Marom; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Implementation of Perda No. 9 in 2009 about retribution service markets is an effort from the government to provide services for merchants. Levy retribution charged to merchants used to cost a oprasional market and to increase services for merchants. Talk to rate retribution charged by merchants pre-set by the Regional Secretary is assisted the DPPKAD which is calculated by multiplying the number of traders as the areaof floor with a rate of retribution pre-set at Perda. The market is as a place for conducting trading deals. The market function itself is one of the principal means to drive and improve the economy. Markets need to be managed, organized and arranged so that the wheels of the economy community area can run smoothly. Retribution is charged to every trader who utilize the facilities of the market. Rate retributionare different, determined by class and place the used market. Occupies a place in the trade market, traders must also obtain a trade license issued by the placement department ofindustry and commerce. This type of research used in this study is qualitative research with qualitative descriptive method that aims to describe, explain and analyze. An informantwho concerned in the implementation of perda is nameli disperindag, UPTD Puri market already implementing regulation 9 of 2009 but still appears constraints in the implementation of the levy charges eventually hamper the realization of the income levy income levy charges that are not in accordance with pre-determined targets. Ineffectiveness of socialization has been done by the Disperindag and UPTD market also makes some traders there is no pleasure to pay the levy. An informant who is involved also came out differences of opinion between disperindag with UPTD Puri market,